Trigger - Griffin, N. (Atheneum, an imprint of Simon & Schuster Children's Publishing Division, 2022)
Didi's father is constantly pressuring her to do better: win at chess, run faster every day, shoot better, hunt better or go hungry; she is not allowed friends, or time off or any pleasures; he always reminds her that they have to be prepared to fight the rest of the world--but what he never tells her is that when she is the best, he plans to hunt her.